My Brother's Keeper : George McGovern and Progressive Christianity - Lempke, Mark A., 1983-; Project Muse. (Boston : University of Massachusetts Press, 2017)
"George McGovern is chiefly remembered for his landslide loss to Richard Nixon in 1972. Yet at the time, his candidacy raised eyebrows by invoking the prophetic tradition, an element of his legacy that is little studied. In My Brother's Keeper, Mark A. Lempke explores the influence of McGovern's evangelical childhood, Social Gospel worldview, and conscientious Methodism on a campaign that brought antiwar activism into the mainstream. McGovern's candidacy signified a passing of the torch within Christian social justice. He initially allied with the ecumenical movement and the mainline Protestant churches during a time when these institutions worked easily with liberal statesmen. But the senator also galvanized a dynamic movement of evangelicals rooted in the New Left, who would dominate subsequent progressive religious activism as the mainline entered a period of decline. My Brother's Keeper argues for the influential, and often unwitting, role McGovern played in fomenting a 'Religious Left' in 1970s America, a movement that continues to this day. It joins a growing body of scholarship that complicates the dominant narrative of that era's conservative Christianity"--Provided by publisher.
George McGovern's soul -- For-prophet education -- Brother George : a politician as churchman -- Pastors, public men, and peacemakers -- Calling America to come home -- Religious leaders for McGovern -- Evangelicals for McGovern -- The Christian Left's failure to launch -- Becoming Sojourners.
Includes bibliographical references and index.
Description based on print version record.
eBooks on EBSCOhost
Keywords: McGovern, George S. -- 1922-2012 -- Influence; McGovern, George S. -- 1922-2012 -- Political and social views; McGovern, George S. -- 1922-2012 -- Religion; United States. -- Congress. -- Senate -- Biography; McGovern, George S. -- 1922-2012 -- Influence; McGovern, George S. -- 1922-2012 -- Political and social views; McGovern, George S. -- 1922-2012 -- Religion; États-Unis. -- Congress. -- Senate -- Biographies; McGovern, George S. -- 1922-2012; United States. -- Congress. -- Senate; Legislators -- United States -- Biography; United States -- Politics and government -- 1945-1989.; Social justice -- Religious aspects -- Christianity -- History -- 20th century; Protestantism -- Political aspects -- United States -- History -- 20th century; Progressivism (United States politics) -- History -- 20th century; Christianity and politics -- United States -- History -- 20th century; Parlementaires -- États-Unis -- Biographies; Protestantisme -- Aspect politique -- États-Unis -- Histoire -- 20e siècle.; Progressisme -- États-Unis -- Histoire -- 20e siècle.; Christianisme et politique -- États-Unis -- Histoire -- 20e siècle.; États-Unis -- Politique et gouvernement -- 1945-1989.; HISTORY / United States / State & Local / General; POLITICAL SCIENCE / General; Politics and government; Christianity and politics; Influence (Literary, artistic, etc.); Legislators; Political and social views; Progressivism (United States politics); Protestantism -- Political aspects; Religion; Social justice -- Religious aspects -- Christianity; United States; 1900-1999; Biographies; History